Responsibility of Perpetrators of Murder with Same-Sex Romance Motive (Study of Decision Number: 64/Pid.B/2022/PN. Kot) - Recca Ayu Hapsari; Zikri Aldino Z. P (Rechtsnormen: Journal of Law, 2024)
Background. It is hoped that the judge will give a severe criminal verdict against the perpetrators of the crime of murder in order to have a deterrent effect on the perpetrators of the crime. Purpose. Gambling is a prohibited act as stipulated in Article 303 of the Criminal Code, 303 bis of the Criminal Code, and Article 27 paragraph (2) of the Law on information and electronic transactions. In verdict number 233/Pid.B/2022/Pn.Cbd the author found a discrepancy in the application of the article, so the problem in this study is "How is the application of the law of online gambling in verdict number 232/Pid.B/2022/Pn.Cbd?". Method. This research uses normative juridical types contained in laws and court decisions, as well as legal norms that exist in society. Results. The consideration of the judge in the verdict of the murder case with same-sex romance motive considers the criminal elements in the indictment, considers the justification and excuse as the basis for removing criminal liability for the defendant and considers the aggravating and mitigating circumstances by stating that the defendant has been legally and convincingly proven guilty of committing the crime of participating in premeditated murder as charged in the first alternative primair indictment of the Public Prosecutor and imposing a sentence on the Defendant therefore with imprisonment for 17 (seventeen) years. Conclusion. The conclusion of this research is the accountability of the perpetrator of the crime of murder with the motive of same-sex romance is the ability of the defendant to be accountable for his actions through the mechanism of the criminal justice process to decide the criminal penalty for the defendant.